The Relationship between Academic Self-Efficacy and Academic Stress in Medical Students of University X in Makassar City - Wahdini, Nurul Azizah; Alwi, Muh Ahkam (Polteknik Ilmu Pemasyarakatan, 2024)
Medical students are generally required to be able to adapt quickly to the learning process because medical students have a very busy learning schedule. It is not uncommon for students to experience academic stress during the learning process because they are unable to accommodate the burden and demands of the learning they receive. This study aims to determine the relationship between academic self-efficacy and academic stress in medical students. The research method used is a quantitative method. Respondents in this study were 249 medical students aged 18-23 years. The results of this study indicate a negative relationship between academic self-efficacy and academic stress in medical students at University X in Makassar City of (r = -550, p = 0.000). The implications of this study are to provide information and references related to the importance of academic self-efficacy as a prevention in reducing the intensity of academic stress in students, especially those majoring in medicine.